Treatment of dermopathy in patients with polycystic ovary syndrome (clinical lecture) - M. A. Gevorkyan (Медицинский совет, 2015)
The article summarizes the current aspects of the pathogenesis of PCOS and hyperandrogenism mechanisms. The treatment of dermopathy using COC and other androgen receptor blockers is substantiated.